The Use of Simplified Learning Materials (SLM) in Physical Education as a Tool in Enhancing Students Learning Experiences - Carla Jobelle Culajara; Anabella Lao (JUMORA: Jurnal Moderasi Olahraga, 2023)
The pandemic has allowed teachers to apply their innate abilities, such as creativity and innovation, and to impart comprehensive knowledge about physical education with simplified learning materials (SLM) that are centered on the contextual needs of students. The objective of the study is to determine the effect of Simplified Learning Materials (SLM) on students' learning performance in Physical Education. The study specifically aimed to determine the following: (1) evaluate the learning performance of the students in Physical Education before and after using simplified learning materials, and (2) identify the said significant differences between the students' mean scores before and after the intervention. The researchers used a pre-experimental design, specifically the One-Group Pretest-Posttest Design. The study was participated by 52 Grade 8 students in one of the secondary schools in the Philippines. Purposive sampling was used in the study. Data analysis was performed using the JASP software (weighted mean and paired t-test). Data revealed that the Shapiro-Wilk test of normality can be used to determine that the data does not deviate from the assumption of normality with a p-value of 0.305, which is greater than 0.05. According to the descriptive table, the post-test result is higher than the pretest result. The mean difference of -2.538 in the Paired Samples T-Test results is significant, with a p-value of 0.002 for the test. The use of Simplified Learning Materials (SLM) helps grade 8 students perform better on tasks and grasp understanding to the lesson related to physical education. This shows that the intervention has a significant effect on the student’s learning performance in Physical Education.  Future researchers can utilize the findings as a foundation to use simplified learning materials (SLM) for further contextualize and address what students need to accomplish. Keywords: JASP Software, Learning performance, Modality, Physical education, Simplified Learning Materials